Soil Infiltration Rate Mapping of Pontianak City using Single Ring Infiltrometer - Perdhana, Radhitya; Muhardi, Muhardi; Sutanto, Yuris (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February Edition, 2024)
Pontianak is a city located in the Kapuas River watershed. These geographical conditions have resulted in the frequent flooding and inundation that happen when the rainfall intensity is high. One of the driving factors for flooding is the soil infiltration capacity. This study aims to map the rate of soil infiltration in the city of Pontianak as a flood mitigation process. Infiltration rate was measured using simple single ring infiltrometer and kriging interpolation was used to map the distribution of infiltration rate. The results of mapping and validation with existing secondary data showed that the northern an eastern area of the study location has a low infiltration rate. The dominant clay deposits found in this area is considered as the cause. Clay deposits are tend to be impermeable.